TRANSFORMING THE HEALTHCARE SYSTEM: THE PUBLIC-PRIVATE HEALTHCARE DICHOTOMY IN INDIA IN THE ERA OF DIGITAL HEALTH (Proceedings of the International Conference on Public Health, 2021)
Digital health initiatives have become popular in all jurisdictions across the globe. Thedigital health move, though it is envisioned as a cost-effective way to ensure the availability of healthcare services especially for the people who live in rural areas, its success depends on the response ofthe health care system and the state control and regulation. India lacks a comprehensive statesponsored or state-regulated health care system and more than 70 percent of people utilise the privatesector medical services. In this backdrop, the implementation of the National Digital Health Mission(NDHM), announced by the Government of India very recently, will be critical. Thus, this researchpaper strives to bring out the public-private disjunction in the availability and utilisation of publicand private health care facilities, issues of health care financing and legal regulation of clinicalestablishments in the public and private sector. This study uses the doctrinal method and analyses theFive-Year Plans, National Sample Survey Reports, National Health Profile, National HealthAccounts Estimates for India and other Government Reports and independent studies to detail thepublic-private dichotomy. However, this study finds limitations in presenting the current position ofprivate health care service providers due to the unavailability of updated authoritative governmentreports/ studies/ surveys. On reviewing the currents trends in the public and private health caresector, the study finds that the private sector has surpassed the public sector in all means, includinghealth provisioning, utilisation, and financing. The NDHM is a laudable initiative to ensureaffordable health care to millions of people in India. However, any move to implement it, leaving thefundamental issue of deep-rooted public-private dichotomy existing in the healthcare sector will bedetrimental. It will result in a digital divide in the public and private healthcare sector and grossviolation of patients’ rights and mismanagement of health information.
Keywords: digital health, National Digital Health Mission, private healthcare sector, utilisation of healthcare service